An empirical analysis of legal insider trading in the Netherlands - Hans Degryse; Frank de Jong; Jérémie Lefebvre (Center for Economic Studies and ifo Institute (CESifo), 2009)
In this paper, we employ a registry of legal insider trading for Dutch listed firms to investigate the information content of trades by corporate insiders. Using a standard event-study methodology, we examine short-term stock price behavior around trades. We find that purchases are followed by economically large abnormal returns. This result is strongest for purchases by top executives and for small market capitalization firms, which is consistent with the hypothesis that legal insider trading is an important channel through which information flows to the market. We analyze also the impact of the implementation of the Market Abuse Directive (European Union Directive 2003/6/EC), which strengthens the existing regulation in the Netherlands. We show that the new regulation reduced the information content of sales by top executives.
Keywords: G14; G28; K22; 330; insider trading; financial market regulation; Insiderhandel; Führungskräfte; Informationswert; Wertpapierhandel; Börsenkurs; Insiderrecht; EU-Wirtschaftsrecht; Niederlande